Cationic Polyelectrolyte Bridged Boron Nitride Microplatelet Based Poly(vinyl alcohol) Composite: A Novel Method toward High Thermal Conductivity. Issue 17 (8th July 2019) - Li, Huayuan; Gao, Yuan; Zhu, Pengli; Du, Xiaomeng; Yu, Xuecheng; Ma, Longquan; Li, Gang; Sun, Rong; Wong, Ching‐Ping
Abstract: Efficient heat dissipation becomes increasingly important for high power density devices. 2D layered material hexagonal (BN) has gained extensive attention due to its superior heat conduction performance. However, phonon scattering within the polymer composites makes it fail to reach the full potential of BN. In this work, a cationic polyelectrolyte namely branched polyethyleneimine (PEI) is utilized to building bridged structure between BN and poly(vinyl alcohol) (PVA) polymer. The PEI on the BN surface can help to restrict the agglomeration of the fillers to achieve more uniform distribution then building more effective thermal conductive channels. When filled with BN@PEI particles at the loading of 50 vol%, the thermal conductivity is increased to 14.22 W m −1 K −1 . The ultrahigh of thermal conductivity is mainly attributed to this linear polyelectrolyte bridged molecular which can be acted as a phonon transfer pathway between BN and PVA matrix and lead to the remarkably decrease of interface thermal resistance. In addition, mechanical performance of the BN@PEI/PVA composites is also attributed to the enhanced interfacial affinity between filler and polymer matrix. This work provides an effective universal strategy to design polymer composites to improve the efficiency of heat dissipation in next‐generation high power products. Abstract : Boron nitride (BN)@polyethyleneimine(PEI)/poly(vinyl alcohol)(PVA) composite film with a high thermal conductivity of 14.22 W m −1 K −1 is fabricated via doctor blading process. The interface thermal resistance within the composites is remarkably decreased through building bridged structure between BN and PVA matrix with PEI as a bridging agent.